1991
DOI: 10.1620/tjem.163.245
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Central Diabetes Insipidus in a Case of Malignant Lymphoma.

Abstract: A 37-year-old man was diagnosed as malignant lymphoma infiltrating in the central nervous system with hypopituitrism and secondary glucocorticoid deficiency. In this case, plasma arginine vasopressin (AVP) increased, but glucocorticoid administration decreased plasma AVP and increased urine volume with a reduction in urinary osmolality, indicative of the presence of glucocorticoid-induced diabetes Insipidus. At the terminal stage, plasma AVP did not increase in response to the withdrawal of glucocoticoid and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Hence, patients with adrenocorticotropic hormone deficiency will have increased tonic ADH activity and subsequently reduced capacity for free-water excretion. When their patient had steroid accumulation, the ability to excrete free water was restored ( Huang et al 2005 , Ohta et al 2006 ). Therefore, in our patient, classical features of DI developed soon after commencing dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, patients with adrenocorticotropic hormone deficiency will have increased tonic ADH activity and subsequently reduced capacity for free-water excretion. When their patient had steroid accumulation, the ability to excrete free water was restored ( Huang et al 2005 , Ohta et al 2006 ). Therefore, in our patient, classical features of DI developed soon after commencing dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…A combined diagnosis of DI and SIADH, as in the case presented here, was not reached without careful consideration of other possible diagnoses. In cases of hypopituitarism, it has been reported that low cortisol levels seen in ACTH deficiency can mask symptoms of DI [ 9 , 10 ]. Cortisol has a direct inhibitory effect on endogenous ADH secretion; hence, ACTH deficiency increases tonic ADH activity, reducing the capacity for excretion of free water.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Plasma concentration of arginine vasopressin thus increases in patients with glucocorticoid deficiency, which may lead to hyponatraemia that mimics syndrome of inappropriate antidiuresis. 8 Steroid replacement inhibits synthesis of arginine vasopressin, which corrects the hyponatraemia 8 or, as in this case, unmasks central diabetes insipidus.…”
Section: Long Answermentioning
confidence: 96%